ISSUES OF ENHANCING THE EFFICIENCY OF INNOVATIVE MANAGEMENT IN THE TEXTILE AND GARMENT ENTERPRISES IN UZBEKISTAN - Sarimsaqov Doniyor,; Nurmuhammedov Husniddin Hursandbek o'g'li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article outlines ten strategies to achieve these goals, with a focus on the unique context of Uzbekistan.